Evaluation of software technical quality for collecting data from patients under palliative care - Jéssica de Fátima Gomes Pereira; Letícia Pontes; Mitzy Tannia Reichembach Danski; Solena Ziemer Kusma Fidalski; Juliana de Oliveira dos Santos; Maria Gorete de Brito Cunha; Mairla Cristina Silva Mota; Edmilson Bezerra Cruz Júnior (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to evaluate software technical quality for collecting data from patients under palliative care. Methods: this is methodological technology evaluation research, according to the technical standard International Organization for Standardization/International Electrotechnical Commission 25040-2011, developed from August 2021 to August 2023. Eight nurses and eight information technology professionals participated as judges, who evaluated six quality characteristics and 23 subcharacteristics. Items that reached a percentage of agreement greater than 70% were considered suitable. Results: the characteristics evaluated by nurses/information technology professionals received the following percentages of agreement, respectively: functional suitability (94%-84%); reliability (100-70%); usability (89.9-66.8%); performance efficiency (95.8%-86.1%); compatibility (95.8-79.6%); and safety (96%-83.4%). Conclusions: the software was considered suitable in quality evaluation to offer support to nurses in collecting patient data under palliative care, with the potential to operationalize the first Nursing Process stage.